Algorithmic mediation and virtual engagement in smart tourism: An expectation–confirmation model of trust and travel intention among Gen Z tourists in Thailand - Liang, Yingtao; Surinta, Olarik; Tirakoat, Suwich (Edelweiss Applied Science and Technology, 2025)
Tourism in the digital era is increasingly influenced by algorithmic recommendation systems and immersive online interactions. This study examines how algorithmic mediation and virtual engagement jointly affect Chinese Generation Z tourists' trust and travel intentions in Thailand, a leading destination for smart tourism. Guided by the expectation–confirmation model (ECM), we tested a structural equation model using survey data from 512 respondents. The findings indicate that algorithmic mediation enhances both expectation confirmation and virtual engagement. Virtual engagement significantly fosters trust and directly predicts travel intentions, while trust emerges as the strongest mediator linking digital interactions to behavioral outcomes. Multi-group analysis reveals that prospective travelers rely more on virtual engagement to build trust than experienced travelers, highlighting the conditional role of prior travel experience. This research contributes to the smart tourism literature by integrating algorithmic mediation and virtual engagement into the ECM framework, emphasizing their crucial roles in shaping Generation Z tourists' digital decision-making. Practical implications suggest that tourism platforms should refine algorithmic design and interactive features to strengthen trust and effectively convert online engagement into actual travel behaviors.